"A Step Towards Silence": Samuel Beckett's The Unnamable and the Problem of Following the Stranger. Issue 4 (1st October 2016) - Marais, Mike
Summary: In this article, I argue that Samuel Beckett's The Unnamable evinces the kind of aesthetic ambivalence that Theodor Adorno, in Aesthetic Theory, ascribes to the artwork's location both in and outside of society. By tracing the metaphors used in the narrator's depiction of the act of narration, I demonstrate that this novel self-reflexively articulates and meditates on its ambivalent position in society. Thereafter, I relate the work's suspicion of its medium, and therefore its estrangement from itself, to its critique of community's norms of recognition, which are embedded in language. Finally, I reflect on the potential effect of the text's aesthetic ambivalence on the reader.